The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0146246
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Carcinogenic Human Papillomavirus Genotypes and Association to Cervical Lesions among Women in Fez (Morocco)

Abstract: ObjectivesTo determine the distribution of cervical high-risk human papillomavirus genotypes and their association to cellular abnormalities in women from Fez and its neighborhood.MethodsWomen attending the Hassan II University Hospital for cervical pap smears were recruited after an informed consent. Interviews and two cervical samples were performed for each woman. Cervical samples were used for cytological analysis and HPV DNA detection. HPV was typed using a method based on multiplex PCR with fluorescently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…In this study, we found a significantly higher 481 prevalence of HPV infection in women living with HIV/AIDS (74.50%) and HR-HPV types were present in the vast majority of cases (75%). These findings highlighted that the HPV prevalence in the HIVpositive Moroccan women was significantly higher than observed in the general population (15.7%-43.1%) [6][7][8]. This seems to be in line with other previous reports which documents high proportion of HIVinfected women carrying varieties of HR-HPV types [27,28].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, we found a significantly higher 481 prevalence of HPV infection in women living with HIV/AIDS (74.50%) and HR-HPV types were present in the vast majority of cases (75%). These findings highlighted that the HPV prevalence in the HIVpositive Moroccan women was significantly higher than observed in the general population (15.7%-43.1%) [6][7][8]. This seems to be in line with other previous reports which documents high proportion of HIVinfected women carrying varieties of HR-HPV types [27,28].…”
Section: Discussionsupporting
confidence: 90%
“…This result seems to be in line with previous reports [36,44]. In contrast, this molecular epidemiology profile was not consistent with observed in HIV-negative women [6][7][8] or women with CC in Morocco [9][10][11][12], in whom HPV 16 and 18 predominate. Such discrepancies between groups (HIVpositive and HIV-negative) has been reported in previous studies and may partly due to immune system deficiency [30,45].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, because of the cultural traditions, the limitation of this study is the lack of data about the sexual partner, extramarital relationships (for wives and husbands), sexual life and practice that are still taboo subjects. Considering women with normal cervical cytology, when we compared the overall HPV prevalence among Tunisian women with that from neighboring Northern African countries, we reported that it was higher than that of Algeria (5.3%) [22], but lower than that of Morocco (34.3%) [30]. Additionally, we found relatively high HPV prevalence compared to Arab-Muslim countries from the Middle-East [31–33] but substantially lower than that reported by other studies of the Sub-Saharan countries [34, 35] and Mediterranean Europe [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Certain strains of HPV are associated with different risk levels of transformation into genital tract in both males and females (13,(15)(16)(17). High-risk HPV16 and HPV18, which are found in high frequencies in cervical cancer, account for approximately two-thirds of all cervical carcinomas worldwide (HPV16 as the most frequent type) (16)(17)(18)(19)(20)(21)(22). associated with an increased risk of cervical cancer development (23).…”
Section: Introductionmentioning
confidence: 99%